Eksplorasi Kualitatif Faktor Penghambat Adopsi Teknologi Rainwater Harvesting di Daerah Rawan Kekeringan - Ismail, Syahrul Rezi; Mutmainnah, Mutmainnah; Irmawaty, Irmawaty; Ali, Aisyah Madiana (Civiliza Publishing, 2025)
This qualitative research aims to explore in depth the factors inhibiting the adoption of Rainwater Harvesting (RWH) technology in drought-prone communities, focusing on non-technical aspects that are socio-cultural, perceptual, and psychological. This study uses a phenomenological approach through qualitative methods. Data was collected from communities in drought-prone areas through in-depth interviews and Pumped Group Discussions (FGDs). Data analysis was carried out thematically to identify key patterns and themes. This study reveals five main themes as inhibitors of RWH adoption: (1) Public perception that rainwater is